2019
DOI: 10.14356/kona.2019015
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Filler Content and Shape in Polymer Nanocomposites

Abstract: Car tires, sealing caulk and high-voltage cable insulators are prime examples of commercially available and widely used composites of polymers containing nanostructured particles. In fact, myriads of applications can be realized but the usefulness of such nanocomposites depends heavily on composition, morphology, concentration and dispersion homogeneity of the nanoparticle filler in the polymer matrix. Optimizing these characteristics while ensuring economically feasible fabrication, determines the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 283 publications
(267 reference statements)
0
15
0
Order By: Relevance
“…This structure forms as the viscous filament is deposited, flows, and solidifies into a flattened morphology. The Bi 2 O 3 particle agglomeration directly observed by SEM and micro‐CT analysis increases as the additive concentration increases, which is expected at high additive loadings., 26,38 The micron‐scale voids observed across the fracture surfaces of the tensile test specimens are likely due to pullout of the additives from the polymer upon fracture. An increase in agglomeration and poor interfacial adhesion between the Bi 2 O 3 and the polymer results in an increase in stress concentrations throughout the material and is the likely cause for the reduction of strength observed at the 30 wt% concentration 39…”
Section: Discussionmentioning
confidence: 99%
“…This structure forms as the viscous filament is deposited, flows, and solidifies into a flattened morphology. The Bi 2 O 3 particle agglomeration directly observed by SEM and micro‐CT analysis increases as the additive concentration increases, which is expected at high additive loadings., 26,38 The micron‐scale voids observed across the fracture surfaces of the tensile test specimens are likely due to pullout of the additives from the polymer upon fracture. An increase in agglomeration and poor interfacial adhesion between the Bi 2 O 3 and the polymer results in an increase in stress concentrations throughout the material and is the likely cause for the reduction of strength observed at the 30 wt% concentration 39…”
Section: Discussionmentioning
confidence: 99%
“…Often, only the bioactive property of hydroxyapatite nanoparticles is used to render PLGA scaffolds osteoconductive, either by hydroxyapatite coating 28 or admixing 25 . To also exploit the reinforcement effect of the nanoparticles, higher particle contents are desirable while at the same time, particle agglomeration within the polymer matrix should be avoided 29 . Avoiding particle agglomeration is more challenging at higher filler contents, requiring lengthier and more energy intense processing to distribute particles within the polymer matrix 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This method improves the mixing and compatibility of filler particles in the polymer matrix. However, it results in high leakage current, dielectric losses, and agglomeration when filler content increases near the threshold limit 55,56 . Several works have been reported that ferroelectric materials can be polarized and aligned when they are brought under an electric field during the curing process 47,57,58 .…”
Section: Introductionmentioning
confidence: 99%